Variation of color with baking time in snacks made with pregelatinized cassava. Issue 9 (12th August 2021) - Cazzaniga, Amanda; Brousse, María M.; Linares, Ramón A.
Abstract : Abstract: Color is an importantaspect when formulating products, as the consumer will evaluate this aspect in the first instance. There is a growing interest in non‐wheat producing regions to replace it with local sources of starches. However, the substitution of wheat flour affects characteristics such as texture, flavor, and color of the intermediate and final products. The objective of this work was to determine if the variation of the baking time allows reducing the color difference that the replacement of flour generates by dehydrated cassava puree (DCP). For that, four replacement levels were evaluated using the CIE‐L * a * b * and CIE‐L * C * H * methodology. The browning index and total color difference (ΔE) between samples with different replacement levels and between different stages of production were also evaluated. It was proved that the decrease in the baking time allowed the development of a similar coloring between snacks made with DCP and those made without substitution. Also, moisture values of less than 5% (dry basis) were obtained in the snacks. The browning index increased with the proportion of DCP in flour and doughs, but not in baked snacks. The pregelatinization of starches could be a mechanism to improve the quality of products with substitutions of wheat flour. Practical Application: Color is a critical attribute of foods in consumer acceptance. The accelerated color development that pregelatinized cassava starch produces in the appearance of baked goods can be useful for food development. A quick color development can mean shorter exposure time to heat, which is important for some products with heat‐sensitive components. Also, it is interesting to note that the cassava dehydrated puree is a gluten‐free product.